Agricultural information networks, information needs and risk management strategies: a survey of farmers in Indo-Gangetic plains of India - Mittal, Surabhi; Mehar, Mamta (2013)
The main objective of the study was to identify the information needs of farmers that would enable them manage risk in the wheat, maize and rice cropping systems in Indo-Gangetic Plains (IGP). And also analyze the factors that impact the selection of information sources by farming households.